COMPARISON OF FREQUENCY OF HEPATITIS B AND HEPATITIS C IN PREGNANT WOMEN IN URBAN AND RURAL AREA OF DISTRICT SWAT - Khattak, Sania Tanweer; Marwat, Mumtaz Ali; Khattak, Imran ud Din; Khan, Taj Muhammad; Naheed, Tabassum (Journal of Ayub Medical College Abbottabad, 2009)
Objectives: This retrospective analytical study was carried out to observe the frequency of Hepatitis B and Hepatitis C among the pregnant women of Swat. Methods: The study was carried out from January 2008 to December 2008. It was a retrospective study based on review of records of pregnant women admitted to Labour Room of Obstetrics/Gynaecology Unit, Saidu Teaching Hospital, Swat. Patients were screened for Hepatitis B and C by Immuno Chromatographic Technique (ICT) device. The findings were recorded on proforma and analysed. Those found positive on screening test were confirmed by ELISA. Results: Total number of patients screened was 5607. The frequency of Hepatitis B and C (Combined) was 223 (3.98%), out of which 77 (1.37%) were HBsAg positive, 141 (2.52%) were anti HCV positive and 5 (0.09%) were both HBsAg and anti HCV positive. The frequency of Hepatitis B amongst age groups 14-19 , 20-29, 30-39 and 40-49 years were 2/77, 33/77, 40/77, and 2/77) respectively. The frequency of Hepatitis C amongst age groups 14-19, 20-29,30-39 and 40-49 years was 4/141, 59/141, 67/141 and 11/141 respectively. The frequency of Hepatitis B and C in multigravida was 41/77, 67/141, in grand multigravida it was 20/77, 43/141 and in primigravida it was 16/77, 31/141 respectively. The frequency of Hepatitis B and Hepatitis C amongst urban and rural population was 32 (39.02%) and 50 (60.98%); and 40 (27.40%) and 106 (72.60%) respectively. The frequency of Hepatitis B and C (Combined) in urban, rural population were 72 (31.58 %) and 156 (68.15 %) respectively. Conclusion: HBsAg and HCV was common infections in pregnant women of Swat. Therefore, every pregnant woman undergoing delivery and/or any other surgical procedure must be screened for Hepatitis B and Hepatitis C. Keywords: Screening, Hepatitis, Hepatitis B, Hepatitis C, HBsAg, HCV, Pregnancy, Swat